Prescription Pattern of Psychotropic Drugs at the Psychiatry Outpatient Department of a Tertiary Hospital in Southeastern Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: At present, magnitude of psychiatric diseases occurring worldwide is a growing concern which implies the focus on rational prescribing of psychotropic drugs in public health point. So, the study aims to assess the prescription pattern of psychotropic drugs at the Psychiatry Outpatient Department of a tertiary hospital in Bangladesh.Materials and methods: This cross-sectional study was conducted among 470 patients attended the Out-Patient Department of Psychiatry in Chittagong Medical College Hospital from February, 2023 to January, 2024. Participants were selected consecutively and data were collected by a structured case record form. All ethical issues in different stages of study and quality control of data were maintained strictly.  Results: From the total participants (470) in the study, 30.4% were in the age group 20-29 years in which male were predominant (54.7%). Schizophrenia was the (19.6%) most frequent diagnosis followed by Bipolar mood disorder (16.1%). Among male, Bipolar mood disorder (19.5%) was more common while among female schizophrenia (24.4%) was more common. Antipsychotics (70.2%) were the most commonly prescribed psychotropic drugs followed by antidepressants (50.6%), mood stabilizer (38.9%) and sedative-hypnotics (37.4%). It was found that average number of psychotropic drugs per prescription was 2.2±1.0 (Mean ± SD).Conclusion: The study findings suggest to carry out further studies which would be impactful for improving the prescription pattern of psychotropic drugs to ensure better patient outcome.   JCMCTA 2025 ; 36 (1) : 38-43